2006
DOI: 10.1071/zo06001
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent effect of social environment on immune response and sexual signalling in male zebra finches

Abstract: Variation in avian immune response can be influenced by social environment. This is of particular interest in the context of immunomediated sexual behaviour because social environment may subsequently affect a bird’s relative investment in immunocompetence versus sexual signalling. I tested whether the effect of social environment on immune response and sexual signalling depends on socio-sexual status using male zebra finches (Taeniopygia guttata). To do this, I manipulated social environment (‘same sex’ versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…These results are consistent with those of previous experiments showing that bill color of female American goldfinches functions as a signal of competitive status in interactions with other female goldfinches (Murphy et al, 2009), but does not appear to function in other social contexts (Murphy et al, 2009. In addition, our findings add to a growing body of literature showing that socially-mediated change in expression of a dynamic status signal can affect the outcome of future competitive interactions (Zuk and Johnsen, 2000;Setchell and Dixson, 2001;Gleeson, 2006;Cornwallis and Birkhead, 2008;Karubian et al, 2011;Rhodes and Schlupp, 2012;Dey et al, 2014). Taken together, these results challenge traditional models of condition-dependent signaling that assume that signals reflect, but do not influence, the physiological processes that mediate competitive ability (Rubenstein and Hauber, 2008;Tibbetts, 2014;Vitousek et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with those of previous experiments showing that bill color of female American goldfinches functions as a signal of competitive status in interactions with other female goldfinches (Murphy et al, 2009), but does not appear to function in other social contexts (Murphy et al, 2009. In addition, our findings add to a growing body of literature showing that socially-mediated change in expression of a dynamic status signal can affect the outcome of future competitive interactions (Zuk and Johnsen, 2000;Setchell and Dixson, 2001;Gleeson, 2006;Cornwallis and Birkhead, 2008;Karubian et al, 2011;Rhodes and Schlupp, 2012;Dey et al, 2014). Taken together, these results challenge traditional models of condition-dependent signaling that assume that signals reflect, but do not influence, the physiological processes that mediate competitive ability (Rubenstein and Hauber, 2008;Tibbetts, 2014;Vitousek et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Stressresponses may result from physiological challenges such as nutritional deficiencies, infection, physical trauma, or changing abiotic conditions (e.g., Hill, 2014;Schulte, 2014), but they also can be elicited by psychological phenomena such as perceived predation risk and competitive social interactions (Buchanan, 2000;Creel et al, 2013;Wingfield, 2013). For example, many studies have shown that social defeat, in which an individual loses a competitive contest with a rival, induces a wide variety of both transient and persistent detrimental and compensatory physiological changes consistent with stress-responses in a variety of vertebrates (see Buwalda et al, 2005;Hostetler and Ryabinin, 2013 for general reviews), including birds (e.g., Zuk and Johnsen, 2000;Carere et al, 2001Carere et al, , 2003Gleeson, 2006;Hawley, 2006;Hawley et al, 2006). Different sources and kinds of stressors can yield dramatically different physiological responses, involving a variety of pathways, neurotransmitters, and target tissues (Buchanan, 2000;Armario et al, 2012;Hostetler and Ryabinin, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such preferences are clearly present in the population studied by Burley [14], and Pariser et al [25] report that females responded more often with positive signals in reaction to courtship by red-banded males (yet the scoring was not done blindly). As mentioned earlier, color band preferences were found to be absent in our two zebra finch populations (unpublished data), and nothing is known about band color preferences in the populations studied by Gleeson [39] and Ratcliffe and Boag [24]. So the hypothesis of a joint occurrence of female preferences for red bands and an effect of red bands on courtship rate might deserve further investigation.…”
Section: Discussionmentioning
confidence: 50%
“…These are the previously mentioned experiment by Pariser et al [25] (data extracted from their Fig. 2 using the software Engauge Digitizer V. 4.1, http://digitizer.sourceforge.net ), two experiments (on separate sets of birds housed in different group sizes) reported by Gleeson [39] , and two experiments (on the same set of birds but with colors swapped among males) reported by Ratcliffe and Boag [24] (data taken from their Table 1B ). We further included the study by Burley et al [14] who reported rates of extra-pair courtship behavior by red- and green-banded males.…”
Section: Methodsmentioning
confidence: 98%